BUSINESS ETHICS EDUCATION AT HIGHER SCHOOLS TO PREPARE STUDENTS FOR BEING ETHICS BUSINESSMEN - Soesatyo, Yoyok (International Business Education Journal, 2008)
It is important that business ethics education be conducted and socialized to students at higher schools. Non-ethics phenomena and crisis at many different life sectors may happen due to ethics education neglect in educational process at schools, including at higher schools. Whatever is the students’ profession, they will be always taken part in business activities either as producer, consumer, workers, or other stakeholders, because business is a modern phenomenon separated from society life. Therefore, we must pay attention to the ethics educational process. In the process, lecturers have very important roles to socialize and internalize ethics values to students. Their function in the process are someone being models and information resources, someone selecting and determining the materials and text books used by students, developing educational process, and creating conducive learning environment.